Diffusion MRI in early cancer therapeutic response assessment. (15th January 2016) - Galbán, C. J.; Hoff, B. A.; Chenevert, T. L.; Ross, B. D.
Abstract : Imaging biomarkers for the predictive assessment of treatment response in patients with cancer earlier than standard tumor volumetric metrics would provide new opportunities to individualize therapy. Diffusion‐weighted MRI (DW‐MRI), highly sensitive to microenvironmental alterations at the cellular level, has been evaluated extensively as a technique for the generation of quantitative and early imaging biomarkers of therapeutic response and clinical outcome. First demonstrated in a rodent tumor model, subsequent studies have shown that DW‐MRI can be applied to many different solid tumors for the detection of changes in cellularity as measured indirectly by an increase in the apparent diffusion coefficient (ADC) of water molecules within the lesion. The introduction of quantitative DW‐MRI into the treatment management of patients with cancer may aid physicians to individualize therapy, thereby minimizing unnecessary systemic toxicity associated with ineffective therapies, saving valuable time, reducing patient care costs and ultimately improving clinical outcome. This review covers the theoretical basis behind the application of DW‐MRI to monitor therapeutic response in cancer, the analytical techniques used and the results obtained from various clinical studies that have demonstrated the efficacy of DW‐MRI for the prediction of cancer treatment response. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Diffusion‐weighted MRI (DW‐MRI) is sensitive to cellular changes and has been evaluated extensively as a quantitative and early imaging biomarker of the therapeutic response. DW‐MR can be applied to many different solid tumors to detect changes in cellularity as measured by an early increase in the apparent diffusion coefficient (ADC) of water molecules within the lesion. An overview of DW‐MRI acquisition protocols, quantitative image analysis approaches and applications implementing DW‐MRI for the early prediction of cancer treatment response is presented.